2015
DOI: 10.3748/wjg.v21.i14.4261
|View full text |Cite
|
Sign up to set email alerts
|

Biliary tract intraductal papillary mucinous neoplasm: Report of 19 cases

Abstract: BT-IPMN is a rare biliary entity. Complete resection of the tumor is associated with good survival, even in patients with malignant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 23 publications
2
43
0
Order By: Relevance
“…Intrahepatic IPNBs are more similar to IPMN than the extrahepatic type histopathologically. 12 In a study published by Wang et al with 19 cases, 10 out of 19 tumor showed mucin secretion [14]. The frequency of phenotypes in IPNBs are pancreaticobiliary (45%), gastric (25%), intestinal (20%) and oncocytic (10%), respectively.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Intrahepatic IPNBs are more similar to IPMN than the extrahepatic type histopathologically. 12 In a study published by Wang et al with 19 cases, 10 out of 19 tumor showed mucin secretion [14]. The frequency of phenotypes in IPNBs are pancreaticobiliary (45%), gastric (25%), intestinal (20%) and oncocytic (10%), respectively.…”
Section: Discussionmentioning
confidence: 96%
“…6 Again in two series with 19 and 32 cases showed almost 50% malignancy with IPNB. 14 Zen et al indicates in their study that IPNB is a more aggressive tumor than IPMN-P and the prognosis of patients with invasive IPNB is poorer than IPMN-P. 9 Focal dilatation of extra or intrahepatic biliary tree, intraductal masses and growth pattern through the interior wall are considered as a warning to suspect from IPNB.…”
Section: Discussionmentioning
confidence: 99%
“…IPMN usually arises from the pancreatic duct. In the literature, there are few reported cases of IPMN arising from the biliary tree [9, 11, 12, 13, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…1 This clinical entity is a precursor of invasive carcinoma, and 40-80% of resected IPMN-Bs contain invasive components. 2 Therefore, most cases are treated surgically. However, conservative therapy was considered for inoperable patients with compli- Intraductal papillary mucinous neoplasm of the bile duct (IPMN-B) is frequently found and has recently been recognized as a precancerous lesion leading to invasive carcinoma characterized by papillary growth of the ductal epithelium with rich mucin production and cystic dilatation of the hepatic duct.…”
Section: Introductionmentioning
confidence: 99%